2015
DOI: 10.1002/eco.1634
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term performance of in‐stream restoration measures in boreal streams

Abstract: Studies on the effectiveness of in-stream restoration have generally reported increased habitat heterogeneity, but biological responses have been more variable. One hypothesis states that the restored habitat structure does not persist through time, resulting in fading biological responses. We studied the durability of in-stream restoration in northern and central Finland by assessing short-term (0-1 years) and long-term (≥10 years) changes in habitat structure after restoration. In 2010, we repeated the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
(117 reference statements)
2
18
0
Order By: Relevance
“…In‐stream restoration typically uses heavy machinery to conduct the restoration work, usually with the desired outcome of increasing streambed heterogeneity (Marttila et al. ). On a negative side, restoration operations may eradicate macrophytes, causing a massive reduction of macrophyte biomass across large spatial scales (Muotka and Laasonen , Louhi et al.…”
Section: Discussionmentioning
confidence: 99%
“…In‐stream restoration typically uses heavy machinery to conduct the restoration work, usually with the desired outcome of increasing streambed heterogeneity (Marttila et al. ). On a negative side, restoration operations may eradicate macrophytes, causing a massive reduction of macrophyte biomass across large spatial scales (Muotka and Laasonen , Louhi et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gardeström et al (2014) noted that the stakeholders were concerned about returning boulders into the stream channel because they expected water to disappear and fishing to become difficult. Their results, as well as those of many others (e.g., Marttila et al 2015), have shown, however, that restoration typically decreases flow velocity and increases water depth.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, channel and hydraulic complexity, channel width, and mean water depths will generally increase, whereas flow velocities will decrease (Marttila et al 2015). These changes are expected to increase species diversity and the production of the target fish species.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more information may not address the larger ‘field of dreams’ problem that seems to be occurring at this site and is noted elsewhere (e.g. Boreal forest stream in Finland, Marttila et al, ). Although legislation in Ontario, Canada, requires species‐at‐risk habitat availability be included in designs, it may not be successful for (re)establishing populations in these restored channels.…”
Section: Discussionmentioning
confidence: 95%